Saturday
March 25, 2017

Post a New Question

Posted by on .

Simplify the expression. Write your answer using only positive exponents.
Explain as well.

1. (8x)^3*8^-4
2. 2x^-5*y^-3
3. (4x^4y^-3)^-2
4. 1/(3x)^-2

  • I NEED HELP (ALGEBRA) - ,

    ( 8 x ) ^ 3 * 8 ^ ( -4 ) =

    8 ^ 3 * x ^ 3 / 8 ^ 4 =

    8 ^ 3 * x ^ 3 / ( 8 ^ 3 * 8 ) =

    [ ( 8 ^ 3 ) / ( 8 ^ 3 ) ] * ( x ^ 3 / 8 ) =

    x ^ 3 / 8



    2 x ^ ( - 5 ) * y ^ ( - 3 ) =

    2 / ( x ^ 5 * y ^ 3 )



    [ (4 x ^ 4 y ^ ( - 3) ] ^ ( - 2 ) =

    [ ( 4 x ^ 4 / y ^ 3 ) ] ^ ( - 2 ) =

    1 / ( 4 x ^ 4 / y ^ 3 ) ^ 2 =

    1 / ( 16 x ^ 8 / y ^ 6 ) =

    y ^ 6 / ( 16 x ^ 8 )



    1 / ( 3 x )^ ( - 2 ) =

    1 / [ 1 / ( 3 x ) ^ 2 ] =

    1 / [ 1 / ( 9 x ^ 2 ) ] =

    9 x ^ 2 / 1 =

    9 x ^ 2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question